The Beginning of the Time of Troubles in the Golden Horde and the Coup of Navruz Khan - S.P. Karpov (Золотоордынское обозрение)
Research objectives: To clarify the circumstances around the beginning of the Time of Troubles in the Golden Horde in 1359–1360, the overthrow of Kulpa Khan and the coup d’etat of Navruz Khan. Research materials: The author analyzes the whole body of Russian chronicles that mention this event, and for the first time ever publishes a unique text of the Venetian notary Benedetto Bianco, who reported this event. The article contains both the original text in Latin from the cartulary of acts kept in the Venetian State Archive in Italy, and the Russian translation of the source. The novelty and results of the research: In general, the published document confirms and clarifies the account in Russian chronicles that Navruz’s coup occurred in the winter of 1360 and was the result of a conspiracy of the Horde’s nobility. As a result of the coup, Kulpa, his two sons and the emirs supporting him died. In addition to the exact date of the coup, Benedetto Bianco’s record also reveals interesting details about the patronage of Kulpa to Christians, apparently the Catholic monastic orders active in those years in the Golden Horde and the Italian merchants who traded there. The notary’s record vividly portrays the circumstances of the coup that occurred in the steppe, perhaps during a campaign, a journey or hunting trip, rather than at the khan’s residence. Being in the center of events, Bianco is accurate on details and dates, which further increases the value of his description. Both after Navruz’s coup and before it, Tana’s trading post was continuously being rebuilt and settled, still recovering after the long break of the 1340–50s. Transactions for the purpose of acquiring real estate, land and houses, in Tana occupy an important place in the acts of Benedetto Bianco.